Psychoeducation research trends: what the data says? - Saputra, Wahyu Nanda Eka; Nugraha, Ariadi; Suryanto, Farid; Rohmadheny, Prima Suci (Journal of Education and Learning (EduLearn), 2025)
Psychoeducation, merging educational strategies with psychological insights, is pivotal in modern psychology for managing mental health. Understanding psychoeducation trends is vital for its optimization as mental health awareness grows. This study conducted a comprehensive bibliometric analysis of psychoeducation research over the past decade, identifying countries, organizations, researchers, and research theme trends on psychoeducation. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, a bibliometric analysis of psychoeducation literature from 1944 to 2024 was performed. Data were sourced from the Scopus database, focusing on peer-reviewed English journal articles. VOSviewer software provided a quantitative assessment of the field’s structure and dynamics. Findings indicate significant growth in psychoeducation research, particularly from 2020 to 2024, with rising publications and citations. The United States led contributions, followed by the United Kingdom, China, and Australia. Major institutions included the University of Minnesota Twin Cities and Arizona State University, with notable journals such as “frontiers in psychology” and “psychology in the schools.” Influential researchers like Everett L. Worthington, and Bob Algozzine, were prominent. This study outlines psychoeducation’s evolution, highlights future research areas, and offers evidence-based insights for enhancing psychoeducational interventions and mental health outcomes globally.